Molecular genetics of phenylketonuria and tetrahydrobiopterin deficiency in Jordan. Issue 1 (19th May 2020) - Carducci, Carla; Amayreh, Wajdi; Ababneh, Haneen; Mahasneh, Amjad; Al Rababah, Buthaina; Al Qaqa, Kefah; Al Aqeel, Momen; Artiola, Cristiana; Tolve, Manuela; D'Amici, Sirio; Shen, Nan; Yu, Yongguo; et al.
Abstract: Background: Information regarding the prevalence of PKU in the Middle East in comparison to other world regions is scarce, which might be explained by difficulties in the implementation of national newborn screening programs. Objective: This study seeks for the first time to genotype and biochemically characterize patients diagnosed with hyperphenylalaninemia (HPA) at the Pediatric Metabolic Genetics Clinic at the King Hussein Medical Center, Amman, Jordan. Methods: A total of 33 patients with HPA and 55 family members were investigated for pterins (neopterin and biopterin) and dihydropteridine reductase (DHPR) activity in dried blood spots. Patients with HPA were genotyped for phenylketonuria (PKU) and the genes involved in tetrahydrobiopterin (BH4 ) metabolism. Results: In total 20 patients were diagnosed with PKU due to phenylalanine hydroxylase (PAH) deficiency, 2 with GTP cyclohydrolase I (GTPCH) deficiency, 6 with DHPR deficiency, and 3 with the 6‐pyruvoyl‐tetrahydropterin synthase (PTPS) deficiency. Diagnosis was not possible in 2 patients. This study documents a high percentage of BH4 deficiencies within HPA patients. With one exception, all patients were homozygous for particular gene variants. Conclusions: This approach enables differentiation between PKU and BH4 deficiencies and, thus, allows for critical selection of a specific treatment strategies.